The Effect of Thayyibah Expression Habituation on the Tendency of Negative Language Use among Elementary School Students - Siti Lufniyah; Rahman, M. Rifki; Muhaimin; Yahya Mof; Muhamad Sabirin (Yayasan pendidikan dzurriyatul Quran, 2026)
The use of inappropriate language among elementary school students has increasingly become a concern in educational and social contexts, particularly in relation to moral and character development. Within Islamic education, the habituation of thayyibah expressions is considered an essential approach to fostering ethical communication and positive social behavior from an early age. This study aims to examine the effect of thayyibah expression habituation on negative language use tendencies among elementary school students. A quantitative descriptive method was employed using a survey involving 51 third-grade students selected through total sampling. Data were collected through a structured questionnaire and analyzed using descriptive statistical techniques based on percentage distribution. The findings reveal that students’ thayyibah expression habituation was predominantly high, while tendencies toward negative language use were generally low to moderate. These results indicate that stronger thayyibah expression habituation is associated with lower negative language tendencies, highlighting its role in supporting ethical language behavior and moral development in elementary education.